2020
DOI: 10.1159/000509481
|View full text |Cite
|
Sign up to set email alerts
|

Urachal Cancer in Germany and the USA: An RKI/SEER Population-Based Comparison Study

Abstract: Introduction: Urachal cancer (UrC) is a rare but aggressive cancer. Due to its low incidence, structured epidemiological data have only rarely been reported. To date, no valid data on UrC are available for the German population. Methods: Data on incidence and relative 5-year survival of urachal lesions (ICD-10: C67.7) were collected from all populationbased cancer registries in Germany, provided by the Robert Koch-Institut (RKI). Data were anonymized and included age, sex, and general histology (ICD-O-3). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…NGS in seven cases revealed a prevalence of TP53 mutation. Some population-based cohort reported the clinical outcome and prognostic factors in MUT (3,7,12). Hager et al reported 154 and 152 cases of MUT in Germany and SEER database from 2011 to 2015, respectively; the relative 5 year-survival rates were 54.8% in Germany and 64.4% in the United States (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NGS in seven cases revealed a prevalence of TP53 mutation. Some population-based cohort reported the clinical outcome and prognostic factors in MUT (3,7,12). Hager et al reported 154 and 152 cases of MUT in Germany and SEER database from 2011 to 2015, respectively; the relative 5 year-survival rates were 54.8% in Germany and 64.4% in the United States (7).…”
Section: Discussionmentioning
confidence: 99%
“…Some population-based cohort reported the clinical outcome and prognostic factors in MUT (3,7,12). Hager et al reported 154 and 152 cases of MUT in Germany and SEER database from 2011 to 2015, respectively; the relative 5 year-survival rates were 54.8% in Germany and 64.4% in the United States (7). Another population-based study, which summarized 152 cases of MUT in Netherlands, reported that only 13 out of 45 patients in stage IV received chemotherapy, with poor survival (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While macroscopic residues are uncommon, microscopic urachal remnants can be detected in up to 32% of adults [2]. With an incidence of <1 case per 1,000,000 people per year, urachal cancer can rarely arise from these remnants with urachal adenocarcinomas (UrC) accounting for over 90% of cases [3][4][5][6]. Non-cystic type UrC mostly (57%) exhibit a mucinous histology followed by intestinal, not otherwise specified (NOS), mixed, and signet ring cell histology subtypes [4,7].…”
Section: Introductionmentioning
confidence: 99%